2001
DOI: 10.1113/jphysiol.2001.012869
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement and imaging of intracellular Ca2+ and H+ transport in isolated rabbit gastric glands

Abstract: 1. Activation of H(+) secretion in the intracellular canaliculi of parietal cells occurs on an unknown time scale with ill-defined kinetics for the coupling of H(+) secretion and the elevation of intracellular calcium ([Ca(2+)](i)) stimulated by secretagogues. 2. We developed a method to determine H(+) secretion in isolated rabbit gastric glands with spatio-temporal resolution, using the fluorescent indicator Lysosensor Yellow-Blue (LYB). Glands accumulated the dye exclusively in the intracellular canaliculi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 12 publications
4
19
0
Order By: Relevance
“…As shown in Fig. 5, fluorescence of the reporter LysoSensor DND-160 at different emission wavelengths (460 nm or 528 nm) behaved in accordance with the recognized responses (3,31) and suggested the feasibility of emission ratiometric reporting. In control studies, no fluorescence was observed when TVs were not present, indicating that the measurements were not attributable to residual dye.…”
Section: Characterization Of Tubulovesicle Preparation and Its Abilitmentioning
confidence: 79%
See 1 more Smart Citation
“…As shown in Fig. 5, fluorescence of the reporter LysoSensor DND-160 at different emission wavelengths (460 nm or 528 nm) behaved in accordance with the recognized responses (3,31) and suggested the feasibility of emission ratiometric reporting. In control studies, no fluorescence was observed when TVs were not present, indicating that the measurements were not attributable to residual dye.…”
Section: Characterization Of Tubulovesicle Preparation and Its Abilitmentioning
confidence: 79%
“…To perform these studies, the fluorescent reporter LysoSensor DND-160 was used to monitor acidity within isolated TVs. Initially, we evaluated sequestration of this reporter and its ability to monitor pH ratiometrically in isolated TVs (excitation 360 nm; emission at 460 nm and 528 nm) (3,6,19,31). In these protocols, the ratio of emission intensities (460 nm/ 528 nm) was measured in TVs (8-to 10-mg aliquots) loaded with the reporter in 96-well plates and then exposed to ICB containing the protonophores FCCP (20 M) and nigericin (7 M), adjusted to clamp pH levels over the range 3.4 -7.4.…”
Section: Characterization Of Tubulovesicle Preparation and Its Abilitmentioning
confidence: 99%
“…In our previous work we characterized the temporal relationship in real time between acid secretion and Ca 2ϩ changes stimulated by carbachol and histamine observing a striking difference in the kinetics of activation of H ϩ secretion. The acid response to a pulse of carbachol was fast, small, transient, and synchronized with the Ca 2ϩ spike, whereas histamine induced a slow, large, and sustained H ϩ secretion with a long lag time (140 s), which was unrelated to the Ca 2ϩ signal (36). Since the activation of HCl secretion by both types of secretagogues involves the translocation of H ϩ /K ϩ pumps contained in tubulovesicular structures to the plasma membrane and the activation of K ϩ and Cl Ϫ channels (41,46), this raises the question as to which are the coupling mechanisms between the elevation of different second messengers and the activation of secretion.…”
mentioning
confidence: 98%
“…However, measurements of gastric secretion were determined in separate experiments using a radiolabel method with low temporal resolution. To improve the measurement of the kinetics of acid secretion and its relationship to [Ca 2ϩ ] I , we previously developed a methodology using fluorescent dyes to simultaneously measure [Ca 2ϩ ] i and secretion (36). In our previous work we characterized the temporal relationship in real time between acid secretion and Ca 2ϩ changes stimulated by carbachol and histamine observing a striking difference in the kinetics of activation of H ϩ secretion.…”
mentioning
confidence: 99%
See 1 more Smart Citation